Integrasi Teknologi Informasi Akuntansi dan Proteksi Sistem Informasi Akuntansi terhadap Cybersecurity Accounting di Era Digital - Sintiya Cahya Maulany; Ety Meikhati; Putri Intan Prastiwi (Akuntansi Pajak dan Kebijakan Ekonomi Digital, 2025)
This study aims to examine the influence of accounting information technology and accounting information system protection on cybersecurity accounting. Using a quantitative approach, data were collected through a structured survey of 100 respondents, selected using purposive sampling, and analyzed to assess the relationship between the research variables. The research instrument consisted of three main constructs: Accounting Information Technology (X1), Accounting Information System Protection (X2), and Cybersecurity Accounting (Y), each measured using 16 question items. Instrument validity testing revealed that 44 out of 48 items met the validity threshold, with correlation coefficients exceeding 0.300, while reliability analysis indicated Cronbach’s Alpha values greater than 0.60 for all variables, confirming internal consistency. Data analysis was performed using multiple linear regression. The results demonstrate that accounting information technology has a positive and statistically significant effect on cybersecurity accounting (coefficient = 0.264; p < 0.05), suggesting that the integration and optimization of technology in accounting processes contribute to enhanced cybersecurity practices. Conversely, accounting information system protection exhibits a negative and statistically significant effect on cybersecurity accounting (coefficient = -0.149; p < 0.05). This unexpected finding indicates that certain protective measures within accounting information systems may, under certain conditions, hinder cybersecurity performance, potentially due to implementation complexity, inadequate configuration, or user resistance. The regression model as a whole is statistically significant (F = 18.577; p = 0.000), with a coefficient of determination (R²) of 0.277. This implies that the two independent variables together explain 27.7% of the variance in cybersecurity accounting, while the remaining 72.3% is attributable to other factors not examined in this study.